Spigelian Hernia Including the Urinary Bladder: A Rare Potential Cause of Surgical Complication - SADIKOĞLU, BİLAL; KUZAN, BEYZA NUR; TÜNEY, DAVUT (EDURAD, 2019)
Spigelian hernia is a rare type of anterior abdominal wall hernia. While it is itself very rare, seeing urinary bladder in this hernia is even rarer. Here, in this case, we specifically illustrate a rare case of Spigelian hernia including the urinary bladder, diagnosed with computerized tomography.
Keywords: Spigelian hernia; urinary bladder; semilunar line; abdominal; computed tomography; ABDOMINAL-WALL HERNIAS; CT FINDINGS; REPAIR